2017
DOI: 10.1186/s11671-017-2369-1
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Approach for Synthesizing of Fluorescent Carbon Quantum Dots from Tofu Wastewater

Abstract: We present an investigation on carbon quantum dots (CQDs) synthesized from wastewater induced during the production of tofu. We find that tofu wastewater is a good source of raw material in making fluorescent CQDs. The corresponding CQDs can be fabricated simply via hydrothermal reaction to carbonize the organic matter in the yellow serofluid of tofu wastewater. Two sorts of CQDs can be obtained within the deionized water and NaOH solution, respectively, where the CQDs in water (NaOH solution) can emit blue (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
(33 reference statements)
0
28
0
Order By: Relevance
“…The green fluorescent CQDs also show a broad PL peak that shifts with the change of excitation wavelength, which is related to the quantum-confinement effect and edge defects. With the standard PL measurement [ 22 ], the fluorescence quantum yield of the CQDs is 16.7% with an excitation wavelength of 410 nm, where quinine sulfate had been used as the reference. This value is significantly better than the QY (8.95%) of CQDs made from lemon juice in the previous report [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The green fluorescent CQDs also show a broad PL peak that shifts with the change of excitation wavelength, which is related to the quantum-confinement effect and edge defects. With the standard PL measurement [ 22 ], the fluorescence quantum yield of the CQDs is 16.7% with an excitation wavelength of 410 nm, where quinine sulfate had been used as the reference. This value is significantly better than the QY (8.95%) of CQDs made from lemon juice in the previous report [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, we know that NaBH 4 is toxic. Very recently, we have fabricated the green- and blue-emitting CQDs from tofu wastewater without adding any toxic substances [ 22 ]. The CQDs made from food products and/or by-products are considered be safe for biological applications because there is almost no known toxicity in these natural carbon resources.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the corresponding fluorescent QY has not yet reached the requirements for the application as practical devices. The results obtained from experimental [2729] and theoretical [30, 33] research have confirmed that the edge passivation can effectively improve the electronic optical properties of CQDs. Passivation agents are widely used to adjust the fluorescent properties of CQDs [2123].…”
Section: Introductionmentioning
confidence: 85%
“…used dried shrimp as the source material of BCDs and were reasonably made into a traceable drug delivery system for targeted delivery of crude in MCF‐7 cells. N. Mehta et al . synthesized BCDs by using pasteurized milk as a carbon source.…”
Section: Applications Of Bcdsmentioning
confidence: 99%
“…The electron‐donor capabilities of photoexcited BCDs have clear potential in reduction reactions. Zhang et al . presented an investigation of BCDs synthesized from wastewater from the production of tofu.…”
Section: Applications Of Bcdsmentioning
confidence: 99%